2000
DOI: 10.1139/g00-010
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA in peach (Prunus persica L. Batsch) and its use in fingerprinting and testing the genetic origin of cultivars

Abstract: We isolated and sequenced 26 microsatellites from two genomic libraries of peach cultivar 'Redhaven', enriched for AC/GT and AG/CT repeats, respectively. For 17 of these microsatellites, it was possible to demonstrate Mendelian inheritance. Microsatellite polymorphism was assayed in 50 peach and nectarine cultivars. Of the 1300 PCRs carried out, all but two produced amplified products of the expected size. All microsatellites were polymorphic, showing 2-8 alleles per locus. Heterozygosity ranged from 0.04-0.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
135
4
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(160 citation statements)
references
References 15 publications
9
135
4
9
Order By: Relevance
“…However, microsatellites or simple sequence repeats (SSRs) have become the markers of choice for fingerprinting and paternity analyses in most plant species (Gupta & Varshney, 2000) due to their high polymorphism, codominancy and reproducibility. Over 100 microsatellite markers have been so far reported in peach (Cipriani et al, 1999;Testolin et al, 2000;Sosinski et al, 2000;Aranzana et al, 2002Aranzana et al, , 2003Dirlewanger et al, 2002) and many of them are transferable to other related species (Hormaza, 2002;Wünsch & Hormaza, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, microsatellites or simple sequence repeats (SSRs) have become the markers of choice for fingerprinting and paternity analyses in most plant species (Gupta & Varshney, 2000) due to their high polymorphism, codominancy and reproducibility. Over 100 microsatellite markers have been so far reported in peach (Cipriani et al, 1999;Testolin et al, 2000;Sosinski et al, 2000;Aranzana et al, 2002Aranzana et al, , 2003Dirlewanger et al, 2002) and many of them are transferable to other related species (Hormaza, 2002;Wünsch & Hormaza, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite genotypes of mutant sprouts are identical or very similar to each other. Previous studies failed to discriminate them or found only one locus that distinguished between the mutant sprouts and their original cultivars (Testolin et al 2000, Yamamoto et al 2003, Soriano et al 2005. In contrast, N6 and N13 had two and three distinguishable loci, respectively, of the ten loci.…”
Section: Genetic Diversity and Relationships Of The Nangouhi Clonesmentioning
confidence: 83%
“…In horticulture, mutant sprouts of specific cultivars are often used to produce new cultivars (Testolin et al 2000, Martins et al 2003, Yamamoto et al 2003, Hu et al 2005, Soriano et al 2005. Microsatellite genotypes of mutant sprouts are identical or very similar to each other.…”
Section: Genetic Diversity and Relationships Of The Nangouhi Clonesmentioning
confidence: 99%
See 2 more Smart Citations